Experimental methodology for the generation, processing, and interpretation of ultrasonic signals in composite materials (Revista Cientifica Ingenio Magno, 2022)
A structure is a set of parts connected to each other to support loads. When designing a structure for a specific public use application, engineers must consider that it be safe, aesthetic, and easy to maintain, without compromising economics and environmental constraints. To meet these requirements, it is necessary to propose different topologies and structural geometries before choosing the appropriate materials and shapes. The objective of this work is to make more efficient the design of low weight metallic structures through of a parametric design modeled by the finite element method in ANSYS APDL®.A macro was programed inside the ANSYS APDL, in which fundamental data related with the geometry is input. Then, the program search in a database that storage data about geometric characteristics of commercial steel profiles. Finally, the routine stops when a profile size that fulfill with the requirements of strength and stiffness is found. In other words, with a safety factor and a deflection limit, the program searches the minimum profile size that satisfy with both requirements.The contribution of this project is that a general use program is applied to a more specific part of the mechanics, so that we can obtain an efficient design with the least weight and therefore less cost in less time.
Keywords: Metallic structure; parametric design; finite element; structural design